Business Model Canvas : Ez Tools Company / Azwa Suzailin Ahmad Sunazneen - Ahmad Sunazneen, Azwa Suzailin (2020)
Ez Tools Company was established on 2019. Ez is a shortform from words „easy‟ which means we wanted to ease people with our product development. So we had decided to invent a new product development called HandCond. HandCond is a combination of hand and cond from words „aircond‟ which it suits with our objective which we wanted to create a product that can easily carried to anywhere and can ease people to use our product. The word „cond‟ brings the meaning of aircond which we created a portable aircond in mini size and in hand size and can feels like an aircond which we called as HandCond. Ez Tools Company has a unique features on its product. The first thing is their unique colour of their product. HandCond came out with a colour that does not exist in the market such as nude colour and pastel colour. We wanted to make our product different and become a trend in youth society. Other than that, HandCond are provided a packet of five of water capsule per purchase. Water capsule function is to make the product become a cold like an aircond so water capsule is a need when buying our product